Destructive interparental conflict affects Chinese children’s emotional and behavioral problems: Indirect pathways via parent–child attachment and emotional insecurity - Yang, Meirong; Qi, Huan; Meng, Zhaoyan; Duan, Xiangfei; Zhang, Libin (Frontiers in Psychology, 2022)
Background Previous studies have demonstrated that destructive interparental conflict (IPC) is closely related to the emergence of emotional and behavioral problems in adolescents. In addition, in the family system, such conflict also affects the patent–child attachment relationship and emotional insecurity of adolescents. Objectives This study mainly explores the relationship between destructive interparental conflict and adolescents’ emotional and behavioral problems, focuses on the role of parent–child attachment and emotional insecurity, and analyzes whether this relationality plays multiple mediating roles in the influence of destructive interparental conflict on emotional and behavioral problems. Methods Data for the study were obtained through a questionnaire survey conducted on 524 Chinese adolescents from primary and junior high school. Results Structural equation modeling was conducted to test direct and indirect pathways between destructive interparental conflict and Chinese adolescents’ emotional and behavioral problems. Destructive IPC negatively predicted parent–child attachment and parent–child attachment negatively predicted emotional and behavioral problems. Destructive Interparental conflict positively predicted emotional insecurity and emotional insecurity positively predicted emotional and behavioral problems. Discussion The results show that: (1) Parent–child attachment negatively predicted emotional and behavioral problems, and emotional insecurity positively predicted the same. (2) Parent–child attachment and emotional insecurity act in a multiple mediating role between destructive IPC and adolescents’ emotional and behavioral problems. (3) Parent–child attachment and emotional insecurity constitute two indirect pathways between destructive IPC and adolescents’ emotional and behavioral problems, respectively. Conclusion Destructive IPC can adversely affect emotional and behavioral problems among adolescents; destructive IPC plays a damaging role in their emotional security and parent–child attachment, consequently effecting emotional and behavioral problems.